1998
DOI: 10.1590/s1516-31801998000600008
|View full text |Cite
|
Sign up to set email alerts
|

Chédiak-Higashi syndrome: presentation of seven cases

Abstract: CONTEXT: Chédiak-Higashi Syndrome (CHS) is a rare autosomal recessive disease characterized by recurrent infections, giant cytoplasmic granules, and oculocutaneous albinism. OBJECTIVE: To describe clinical and laboratory findings from CHS patients. DESIGN: Case report. SETTING: The patients were admitted into the Allergy and Immunology Unit of the Instituto da Criança, a tertiary public care institution. CASES REPORT: Seven patients had oculocutaneous albinism, recurrent infections and giant cytoplasmic granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
0
14
0
3
Order By: Relevance
“…26,30 This can help in early diagnosis, therapy and bone marrow transplantation (BMT) before the "accelerated phase" of the disease has developed. Haddad et al 31 reported the outcome of BMT in 10 such children-seven from an HLA-identical related donor and three from an HLAnonidentical related donor.…”
Section: Discussionmentioning
confidence: 99%
“…26,30 This can help in early diagnosis, therapy and bone marrow transplantation (BMT) before the "accelerated phase" of the disease has developed. Haddad et al 31 reported the outcome of BMT in 10 such children-seven from an HLA-identical related donor and three from an HLAnonidentical related donor.…”
Section: Discussionmentioning
confidence: 99%
“…Affected patients are more susceptible to bacterial and fungal infections but have a normal resistance to viral infections. The infections mainly occur in the skin and respiratory tract, most frequently associated with Staphylococcus aureus and Streptococcus beta-haemolyticus [4]. Patients with CHS exhibit alterations in neutrophils including neutropenia, decreased deformability resulting in impaired chemotaxsis and delayed phagolysosomal fusion resulting in impaired bactericidal activity [1].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of choice for CHS is Bone Marrow Transplantation (BMT) from a HLA compatible matched donor [1,6]. CHS patients not submitted to BMT; die at the mean age of 10 years [4].…”
Section: Discussionmentioning
confidence: 99%
“…Erythroderma in a patient with failure to thrive, eosinophilia, hepatosplenomegaly, and recurrent infections may suggest Omenn syndrome [47]. Silvery hair, pale skin, and photophobia are seen in children with Chédiak-Higashi syndrome [37,48]. Griscelli syndrome patients have characteristic clinical findings of the skin and hair, including large melanin clumps in the hair shaft, and abnormal skin melanocytes [49,50].…”
Section: Skin and Mucous Membranesmentioning
confidence: 99%
“…Neurologic symptoms are also seen in Chediak-Higashi syndrome. Patients may have cognitive impairment, nystagmus and cerebellar, spinal and peripheral neuropathies [37,48]. Patients with Griscelli syndrome have neurologic clinical manifestations that include seizures, ataxia, and oculomotor and reflex abnormalities.…”
Section: Neurologic Examinationmentioning
confidence: 99%